2013
DOI: 10.1002/oby.20126
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid A is found on ApoB‐containing lipoproteins in obese humans with diabetes

Abstract: In murine models of obesity/diabetes there is an increase in plasma SAA levels along with redistribution of SAA from high density lipoprotein (HDL) to apo-B containing lipoprotein particles, namely low density lipoprotein (LDL) and very low density lipoprotein (VLDL). The goal of this study was to determine if obesity is associated with similar SAA lipoprotein redistribution in humans. Three groups of obese individuals were recruited from a weight loss clinic: healthy obese (n=14), metabolic syndrome obese (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…4A). The curvature of this surface (radius r ≅ 4.2 nm) is complementary to that of HDL (d = 8–11.5 nm), making it immediately clear how SAA monomer binds HDL via this site, with a particular preference for the smaller particles termed HDL 3 [8], and why such binding is favored over larger lipoproteins [5, 10, 11]. The predicted amyloidogenic segments in SAA are located at the ends (residues 2–9 and 67–70) or in the middle (53–33) of this surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). The curvature of this surface (radius r ≅ 4.2 nm) is complementary to that of HDL (d = 8–11.5 nm), making it immediately clear how SAA monomer binds HDL via this site, with a particular preference for the smaller particles termed HDL 3 [8], and why such binding is favored over larger lipoproteins [5, 10, 11]. The predicted amyloidogenic segments in SAA are located at the ends (residues 2–9 and 67–70) or in the middle (53–33) of this surface (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms linking obesity to BBB dysfunction, and subsequent neuronal impairment, memory loss and dementia are not yet fully established. As stated previously obesity has been associated with increased levels of circulating plasma amyloid proteins (Lee et al, 2009 ; Jahangiri et al, 2013 ) and there is some suggestion that peripheral Aβ can impair BBB integrity by pathologically affecting the cerebrovasculature (Su et al, 1999 ). Further support for the relationship between obesity and degeneration of the BBB suggests that high circulating levels of fat impair active transport of consummatory regulatory hormones such as leptin and ghrelin through the BBB (Banks et al, 2004 , 2008 ), perhaps inhibiting their positive roles in synaptic plasticity via actions in the hippocampus (Shanley et al, 2001 ; Diano et al, 2006 ).…”
Section: Obesity and Brain Pathophysiologymentioning
confidence: 86%
“…Higher levels of Amyloid-beta (Aβ, the main component of amyloid plaques) precursor protein (APP) and tau expression have been reported in hippocampal sections from morbidly obese patients without cognitive impairment, compared to a cohort of non-obese controls (Mrak, 2009 ). Indeed increased levels of plasma amyloid proteins have been found in a number of studies of obese individuals (Lee et al, 2009 ; Jahangiri et al, 2013 ) suggesting a possible mechanism linking midlife obesity with the later development of Alzheimer's disease.…”
Section: Obesity and Brain Pathophysiologymentioning
confidence: 99%
“… 1 , 2 Chronic expression of SAA is associated with inflammatory diseases such as cardiovascular disease, rheumatoid arthritis, and obesity. 3 5 Several studies have demonstrated a positive correlation between levels of acute-phase proteins, such as C-reactive protein and SAA, and the risk of development of cardiovascular disease and have suggested that C-reactive protein and SAA may be biomarkers for cardiovascular disease. Plasma levels of SAA were prognostic of 3-year coronary events in patients with coronary artery disease.…”
mentioning
confidence: 99%